2009 International Workshop on Local and Non-Local Approximation in Image Processing 2009
DOI: 10.1109/lnla.2009.5278404
|View full text |Cite
|
Sign up to set email alerts
|

Noise variance estimation in nonlocal transform domain

Abstract: We consider the estimation of the variance of an additive white Gaussian noise corrupting an image.In the proposed approach, we exploit the nonlocal selfsimilarity of images to achieve an improved separation of noise and signal. In particular, we utilize the same adaptive 3-D transform decomposition used in the BM3D (blockmatching and 3-D Þltering) denoising algorithm, where mutually similar blocks are stacked together and jointly processed. An adaptive-size portion of the high-frequency ends of the 3-D transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Nowadays people use the TID2008 for some other purposes than it was originally created [49,50]. Since this image database already contains noisy and reference images, it can be also exploited for testing image filtering efficiency.…”
Section: Tampere Image Database 2008 (Tid) and Used Noise Modelsmentioning
confidence: 99%
“…Nowadays people use the TID2008 for some other purposes than it was originally created [49,50]. Since this image database already contains noisy and reference images, it can be also exploited for testing image filtering efficiency.…”
Section: Tampere Image Database 2008 (Tid) and Used Noise Modelsmentioning
confidence: 99%
“…In its prototype implementation, our algorithm is limited by the accuracy of the MAD estimator and thus cannot reach the accuracy of algorithms (e.g., [17]) that adopt more sophisticated estimators for the estimation of the variance. Likewise, the simplest LS fitting method is not robust to outliers in the scatterplot.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the advanced methods [17] and [18] are developed for AWGN estimation. As shown in our theoretical and experimental analysis, the fact that the variance of the noise is not constant (heteroskedasticity), and depends instead on the signal, does not per se imply an additional need for adaptive segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Even though this would strictly require the independence of the data, i.e. non overlapping cubes, 12 we have experimentally found that the potential underestimation due to overlaps does not significantly affect the final denoising quality.…”
Section: Gaussian-distributed Datamentioning
confidence: 93%
“…which, similarly to (12), give an estimate of the total residual noise variance of the corresponding Wiener filtered group. …”
Section: The Set Of Coordinates Sŷmentioning
confidence: 99%